Results and Lessons Learned from CorPower Ocean’s Full Scale C4 Wave Energy Converter First Ocean Deployment Period (Proceedings of the European Wave and Tidal Energy Conference, 2025)
In this paper, the results from verification stages 1-4 of the CorPower Wave Energy Converter (WEC) technology are presented, including quantitative results from the first full-scale WEC demonstration in 2023 at Aguçadoura, Portugal.The CorPower Ocean WEC technology has demonstrated a step-change improvement in structural efficiency in wave energy, allowing a large amount of energy to be delivered by small, low-cost devices. The structured product verification demonstration program will bring certified and warrantied WEC products to the market by 2026/2027.Following the IEA OES/ ETIP Ocean best practice, the structured product verification of the CorPower WEC technology has undergone concept validation (stage 1), scaled dry and tank testing (stage 2) and scaled dry and ocean testing (stage 3). These preliminary stages have demonstrated CorPower’s patented wavespring technology and initial power production of the concept.Following successful test results though Stage 1 –3 of the structured verification process, Stage 4 has seen successful design and construction of the world’s largest dry-test facility for WECs of its kind, rated at 7.2 MW. The test rig was designed and commissioned in collaboration with ABB and enabled CorPower to fully test and de-risk the C4 PTO system prior to ocean deployment. All functions were tested including the C4 WEC’s unique survival mode designed for robust operation in the harshest ocean conditions involving cyclic loads up to 4MN (400 tonnes).  The C4 WEC was then commissioned and operated at the Aguçadoura site during its first ocean deployment period (Q4 2023).The survivability of the C4 WEC was confirmed by weathering four major storms, with waves reaching 18.5m in height (Hmax) and demonstrating ability to re-commence grid power export after each storm passed. The WEC was regularly fully submerged under wave peaks during these storm events. Mooring and anchor loads have been proven to stay well within the safety envelope during instances of extreme waves, with device motion during survival mode not exceeding 0.2m in heave.Power production model calibration was successful and indicates higher performance vs model in sea-states tested. Direct comparison between the digital twin and measured ocean test data have shown 96-99% goodness of fit. Power has been exported to the Portuguese grid up to peak power generation of 600 kW.This project represents the first time a wave energy device has proven survivability and power export with a device achieving a mass-to-energy ratio of 300te/MW; all previous attempts in wave energy have been an order of magnitude higher. The paper concludes with a discussion of future steps, both within the ongoing testing campaign of the C4 WEC, and with a summary of lessons learnt being taken forward to the C5 device design.